IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH TERHADAP PEMANFAATAN PASAR INDUK AIMAS KABUPATEN SORONG - Momot, Alfaris; Mubalus, Steni Feni Ema; Siswanto, Siswanto (SOSCIED, 2025)
This study analyzes the implementation of the Local Government's policy regarding the optimization of the Aimas Main Market's function as a local economic center in Sorong Regency. The research was motivated by the fact that the Aimas Main Market, despite being built since 2012 and officially inaugurated in 2017 to replace the previously ceded Central Remu Market, has not been utilized for buying and selling transactions. This situation highlights a gap between infrastructure development policy and its effective implementation and utilization by the community. Using a qualitative research approach, data was collected through interviews and questionnaires with key informants, including officials from the Regional Tax and Retribution Management Agency (BPPRD), traders, and the community. The findings indicate that the primary inhibiting factor is the lack of a regulated transportation system for ingress and egress, particularly for traders and buyers from remote areas and Sorong City. Although all physical facilities, such as market stalls and drainage systems, are reported to be 100% ready, the market's activation awaits the final instruction from the Regent. Local traders continue to use the Central Remu Market, which is now an asset of Sorong City, consequently hindering the local economic optimization in Sorong Regency. Therefore, the study concludes that immediate coordination with the Transportation Agency is essential to finalize the transportation system and activate the Aimas Main Market. Keywords : Local Government Policy, Implementation, Main Market, Economic Center